«Էրեբունի»: պատմական ժամանակաշրջանն ու կերպարային համակարգը - Բեգլարյան, Ժաննա (ԱրՊՀ հրատ․)
В статье рассматривается место романа Айка Хачатряна «Эребуни» в ряду его исторических романов. «Эребуни» - первое завершен-ное произведение автора, вышедшее в свет в 1968 году. В основе романа лежит история основания Эребуни-Еревана и провозглашения Биайны городом славы. Действие романа развертывается в 8 веке до н. э. Основной идеологический акцент делается на прославлении мирного строительного труда, совершаемого по твердому убеждению большинства действующих лиц в романе. Состоявшимся образами романа являются царь Аргишти, мастер Амасия, каменщик Арменак, Еразуи, мэр Арцруни, и другие . Роман является живым мостом между 8 веком до н.э. и будущим, овеянным оттенками современности. The article reveals a position of Hayk Khachatryan’s novel “Erebuni” in the rank of his historical novels. “Erebuni” was the first complete work of the author published in 1968. Basis of the novel lies in the history of Erebuni – Yerevan foundation and Biayna’s proclamation as a glory city. The novel’s action is developed in the 8th century B.C. The basic ideological accent is done on the glorification of the peaceful building work, which is the firm belief of the majority of characters in the novel. The main characters of the novel are the king Argishti, master Amasiya, mason Armenak,Yerazuhi, mayor Artsruni and others. The novel is a living bridge between the 8th century B.C. and the future fanned by modern times shades.
Keywords: Պատմություն; Գրախոսություն